Pengaruh Penggunaan Teknologi Pembelajaran Terhadap Motivasi Belajar Matematika Siswa SMP - Wikasari, Reni; Negara, Habibi Ratu Perwira; Kurniawati, Kiki Riska Ayu; Syaharuddin, Syaharuddin; Negara, Habib Ratu Perwira (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
This study aims to examine the relationship between the use of learning technology and motivation for learning mathematics among junior high school students. The participants included 51 junior high school students from grades VII, VIII, and IX, who responded to a questionnaire as the research instrument. The utilization of learning technology was measured through classroom usage frequency, duration of use, and student engagement levels. Meanwhile, motivation for learning mathematics was assessed based on interest in mathematics, confidence in completing tasks, and the desire to acquire additional knowledge. The research findings indicate a positive correlation between the use of learning technology and motivation, as well as academic achievement in mathematics among students.Thus, it is recommended to integrate technology into teaching strategies to enhance students' learning enthusiasm. However, further research is necessary to better understand the influencing factors of this relationship. This study is expected to provide deeper insights for the development of effective teaching strategies aimed at improving the academic performance of junior high school students.